Evaluation of Infectious Diseases Surveillance Data in 2018 in Dr. Behcet Uz Children's Hospital - Elif Kıymet; Elif Böncüoğlu; İlknur Çağlar; Ferhat Zora; Hurşit Apa; Nuri Bayram; İlker Devrim (Galenos Publishing House, 2019)
INTRODUCTION: This cross-sectional descriptive study aimed to evaluate the distribution of the diseases which were reported to the mandatory disease system and the characteristics of the patients in 2018. METHODS: Between January 2018 - December 2018, all patients who were notified according to the 'Ministry of Health, Standard Diagnosis, Surveillance and Laboratory Guidelines of the Communicating Diseases and Notification System' in Dr. Behçet Uz Children's Hospital except rabies risk-contact cases were included in the current study. Data of the patients was collected from medical records. RESULTS: During the study period 392 communicable diseases were notified. Of these, 41 cases were excluded due to recurrence of notified diseases. As a result a total of 351 patients included in the final evaluation. The most frequently reported diseases were varicella diseases (176 cases, 50%), pertussis (35 cases, 10%), and influenza (25 cases, 7.1%). The most frequent notification was made by the emergency department (129 cases, 36.8%). DISCUSSION AND CONCLUSION: There are very few studies on the notification of the communicable disease reports in Turkey, especially in childhood. Evaluation of the notifications of communicable diseases is accurate for the proper epidemiological surveillance,